Uma concepção comunicativa de educação tecnológica - Kominek, Andréa Maila Voss (2011)
The purpose of this study is to identify a philosophical research that argues questions about technological education, reflects on the Communicative Action Theory of Jürgen Habermas, and propounds the communicative conception of technological education as a possibility to take care of, in a wider and more efficient way, the society's necessities. With this objective, it carries out the philosophical fundamentals of the Communicative Action Theory and the technological education; it explores the importance of the language in the theory, pointing out its cultural construction; it argues the culture concept; it approaches the interaction and interdependence among culture, society and technology in the contemporary capitalist society; it traces a historical summary of technical education in Brazil; and points to the importance of preventing a believing and ingenuous posture on technology. Finally, it examines how the technological education, traditionally, connected to "making" and the industry, can contribute, in a communicative conception, that emphasizes the human being dimension, values and stimulates the swap and the dialogue and opts for the reflection instead of the assimilation, for an effectively social production of the technology. It tries to show, in this manner, that the technological education can and must assist the citizen in preparing himself to live the present reality of rapid technological changes, taking advantage of them, and not being dominated for them.